2012
DOI: 10.1007/s00404-011-2210-5
|View full text |Cite
|
Sign up to set email alerts
|

The quality of sexual life in women with gynaecological cancers

Abstract: According to the results obtained from the study, it can be stated that the sexual quality of life of women with gynaecological cancers is moderate and social support, especially support from a significant person, may affect quality of sexual life positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
4
19
3
Order By: Relevance
“…In a study by Rogers et al ( 2008 ) SQOL of women in the study group was 69.6 ± 23.1 and 69.2 ± 23.0 in the control group. Golbasi and Erenel ( 2012 ) showed that sexual satisfaction among women with reproductive system cancer was 52.50 ± 22.87, including 50.07 ± 22.60 among women over the age of 50 and 50.82 ± 22.42 for married women aged 50 and over. A study of women before and after bariatric surgery found that women before the procedure assessed the quality of sex life at 60.0 and women after the surgery −75.0 (Janik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Rogers et al ( 2008 ) SQOL of women in the study group was 69.6 ± 23.1 and 69.2 ± 23.0 in the control group. Golbasi and Erenel ( 2012 ) showed that sexual satisfaction among women with reproductive system cancer was 52.50 ± 22.87, including 50.07 ± 22.60 among women over the age of 50 and 50.82 ± 22.42 for married women aged 50 and over. A study of women before and after bariatric surgery found that women before the procedure assessed the quality of sex life at 60.0 and women after the surgery −75.0 (Janik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the overall summary score in all analyses. The MSPSS is psychometrically sound instrument and has been used before in studies using cancer patients (Cicero, Lo, Gullo, & Lo, 2009;Golbasi & Erenel, 2012;Ozkan & Ogce, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This instrument is preferably short and has been found to be reliable and valid both in its original language [17] and in other language versions [18,19]. The instrument has been used in clinical and non-clinical settings [3,20,21], in various age groups [7,22,23] and in samples with various cultural backgrounds [24-26]. Until today, there is no validated Swedish version of the MSPSS, a prerequisite for international communication and comparisons between studies.…”
Section: Introductionmentioning
confidence: 99%